A Deliberative Independent Central Bank - Erwin Jericha; Martin Schürz (Oesterreichische Nationalbank (OeNB), 2006)
The paper develops a communication game that is applied to the question of central bank policy and independence. The game is about the preferred degree of conservatism of monetary policy and the game setting consists of a principal (politics), an agent (central bank) and an observer (financial market participants). The extent of the welfare losses depends on the degree of knowledge, the endogenized signaling of financial market participants and the probability whether the degree of conservatism in monetary policy is adequate to nature. Consequently, a mechanism to minimize welfare losses of the principal has to be implemented. It is shown how the introduction of an institutional control mechanism with a countervailing goal function will improve the utilities for the principal.
Keywords: E58; E59; E61; C79; 330; accountability; agency losses; principal agent model